Distinct wave profiles relating to a coupled of Schrödinger equations depicting the modes in optics - Islam, Md. Tarikul; Sarkar, Setu; Alsaud, Huda; İnç, Mustafa (Springer, 2024)
Diverse aspects of real-world problems are portrayed through nonlinear Schrodinger equations. This exploration considers a pair of fractional order Schrodinger equations describing important nonlinear instability phenomena which are related to heat pulse, quantum condensates, nonlinear acoustics, hydrodynamics, and nonlinear optics. The improved auxiliary equation and improved tanh schemes are imposed on the governing model which generate a bulk of innovative accurate wave solutions. Plenty of wave solutions achieved in this study could be utilized to characterize the interior mechanisms of intricate phenomena relating to the considered nonlinear models. Some of the solutions are selected to figure out in the sense of contours, 3D and 2D outlines after assigning suitable values to the involved free parameters. The directed techniques are employed to explore appropriate wave solutions of the above-stated nonlinear model for the first time ensuring the unique solutions rather than the results in earlier studies. This present work highlights the competency of used methods celebrating huge appropriate wave solutions of suggested complex nonlinear models and gives a guideline for related future research.
Keywords: Schrodinger model; Improved auxiliary equation approach; Improved tanh scheme; Solitons; Optics